(untitled) (Mustansiria Dental Journal, 2018)
Background: The property of the bleaching light sources is the wide and curved (the negative of the mouth curve) head of exposure. The aim of this study was to, test the efficiency of this devise to bond orthodontic brackets, via unique exposure for the whole teeth, by comparing the rate of the brackets failure with the traditional led light source used in orthodontic brackets bonding which utilizes light exposure for every tooth separately, and evaluating the benefit of time saving through contrasting the time required for bonding with the ordinary led and halogen light sources. Materials and methods: 856Roth 0.22 stainless steel brackets were bonded to 39 patients by using one of the two light sources in the form of three groups; bleaching light group (13 patients / 225 brackets) , ordinary led light group (13 patients /237 brackets), split mouth group( by using combination of the two sources, 13patients / 229 brackets). Results: There is no statistically significant difference between the light source used for bleaching and traditional led light source in bracket failure rates, and the time required for bonding by the bleaching light source is 22% and 5% of that required by ordinary led light and ordinary halogen light respectively. Conclusion: the light sources used for bleaching can be used effectively in bonding of orthodontic brackets with given advantage of saving time and effort.